Design and engineer a domestic-use indoor vertical farming unit - Thong, Emily Yuan Min (Nanyang Technological University, 2022)
Indoor farming technology is being scaled down to domestic-use units to make the process of growing food at home simple and convenient, which could assist the government with achieving their goals of using technology in local food production and increasing Singaporeans’ participation in growing their own food. However, indoor farming setups require high maintenance, hence robotics are increasingly being applied in indoor farming to solve manpower limitations and increase productivity. This study aims to analyze existing domestic-use indoor farming products on the market and develop a design that would better address the needs of users. This study also aims to design and build a six-degree-of-freedom Bluetooth-controlled robotic arm that would be customized and calibrated to harvest produce from planter boxes used by Corridor Farmers, an urban farming startup in Singapore. An investigation into the optimization of the robotic arm design would be conducted, and the full robotic arm would be put through physical and simulation tests to determine its specifications such as repeatability, range, and payload.